The Characteristics of Tsunami Deposit based on Mineralogy Studies - Zul Kamal, Nurul Atiqah (IRC, 2016)
The December 26, 2004 tsunami phenomena that brought by Indian Ocean earthquake, struck the North West Coast of Malaysia has left important imprints in the inundated areas in the form of distinct sedimentary deposits, called as tsunami deposits. Peninsular Malaysia North West coast in Kedah is one of the area that have been affected by the tsunami disaster. This paper covers study of minerals presence in tsunami deposit in Kedah, Malaysia coast, namely Kuala Teriang, Langkawi and Kota Kuala Muda with the minerals content at the area that not affected by tsunami which is Pantai Teluk Batik, Perak as well as comparison with available data of minerals content in tsunami deposit from other established paper.